The Damascus Road of the convert Francisco de Acevedo: From Galicia to Peru (1591-1604) - Tardieu, Jean-Pierre (2023)
A young Galician converso, initiated to the faith of Moses by the women of his family near the Portuguese border shortly before moving to Peru at the end of the sixteenth century, requested in 1603 the absolution of the Holy Office of Lima, obsessed with the salvation of his soul and his mystical experiences. Managing his neurotic mood, the inquisitors tried to take full advantage of a case of little relevance to give themselves the means to end a crypto-Jewish nucleus that had spread to the Indies.